2021
DOI: 10.3389/fpls.2021.804356
|View full text |Cite
|
Sign up to set email alerts
|

The TSN1 Binding Protein RH31 Is a Component of Stress Granules and Participates in Regulation of Salt-Stress Tolerance in Arabidopsis

Abstract: Tudor staphylococcal nucleases (TSNs) are evolutionarily conserved RNA binding proteins, which include redundant TSN1 and TSN2 in Arabidopsis. It has been showed TSNs are the components of stress granules (SGs) and regulate plant growth under salt stress. In this study, we find a binding protein of TSN1, RH31, which is a DEAD-box RNA helicase (RH). Subcellular localization studies show that RH31 is mainly located in the nucleus, but under salinity, it translocates to the cytoplasm where it accumulates in cytop… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 79 publications
0
4
0
Order By: Relevance
“…Tudor proteins are members of a royal superfamily that also contains the Chromo, MBT, PWWP, and plant Agenet domain proteins [ 28 , 29 ]. Since the first Tudor protein discovered in D. melanogaster [ 30 ], these proteins are also found in mouse, human, zebrafish, yeast, and plants [ 31 , 32 , 33 , 34 , 35 , 36 , 37 , 38 , 39 , 40 , 41 ]. Tudor proteins bind to proteins with methylated arginine or lysine residues and take part in cellular processes, such as DNA methylation, RNA metabolism, transcription regulation, DNA damage detection and repair, the P-element-induced wimpy testis (PIWI)-interacting RNA (piRNA) pathway, and the maintenance of genomic stability [ 32 , 42 ].…”
Section: Introductionmentioning
confidence: 99%
“…Tudor proteins are members of a royal superfamily that also contains the Chromo, MBT, PWWP, and plant Agenet domain proteins [ 28 , 29 ]. Since the first Tudor protein discovered in D. melanogaster [ 30 ], these proteins are also found in mouse, human, zebrafish, yeast, and plants [ 31 , 32 , 33 , 34 , 35 , 36 , 37 , 38 , 39 , 40 , 41 ]. Tudor proteins bind to proteins with methylated arginine or lysine residues and take part in cellular processes, such as DNA methylation, RNA metabolism, transcription regulation, DNA damage detection and repair, the P-element-induced wimpy testis (PIWI)-interacting RNA (piRNA) pathway, and the maintenance of genomic stability [ 32 , 42 ].…”
Section: Introductionmentioning
confidence: 99%
“…In RNA turnover, the interplay between the RNA exosome machinery, responsible for 3’-5’ degradation and the processing of various RNA classes, and DEAD-box RNA helicases influences stress granules (SGs) and processing bodies (P-bodies) dynamics [ 92 , 93 ]. These cytosolic ribonucleoprotein complexes are stimulated by various stresses, including oxidative stress, and modulate mRNA translation, storage, and degradation, conserving energy for translational machinery during stress conditions [ 94 ].…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have reported that DEAD-box RNA helicases are involved in root development and stress responses 42 , 71 . In Arabidopsis , AtRH53 showed strong promoter activities in root tips in 6-, 9-, and 16-day-old seedlings and a wounding-induced expression in detached leaves 72 .…”
Section: Discussionmentioning
confidence: 99%
“…For example, tissue culture of root initiation defective1-1 ( rid1-1 ; an RH gene) mutant plants showed that these plants were temperature sensitive for callus, AR, and LR formation from hypocotyl explants in Arabidopsis 41 . Compared with Col-0, Atrh31 mutant seedlings had a shorter primary root length and lower fresh weight, while the Atrh31 mutant lines complemented with the AtRH31 gene rescued the Atrh31 mutant phenotype 42 . Loss-of function of the RH gene AteIF4A-1 reduced the proportion of mitotic cells in the root meristem and disrupted the relationship between cell size and cell cycle progression, thereby reducing Arabidopsis LR formation 43 .…”
Section: Introductionmentioning
confidence: 97%